Impact Mitigation for Transmission Line Project through Public Participation - Iamtrakul, Pawinee; Kritayanukul, Puriched; Nusook, Tattep (Journal of Architectural/Planning Research and Studies (JARS), 2015)
Electricity plays an important role on driving country’s economic development and accommodate to daily life of people. Currently, the demand for electricity raised to approximately 1,200 MW, it is necessary to develop new power plant projects to support an increasing demand. The allocation of electricity network systems required a power transmission to serve between the sources to community which represents as the end users of the system. The development of project causes changes in characteristics of land use surrounding to pass and infringe upon different land ownerships. This process requires the payment for compensation to land owners which reflect on different levels of satisfactions. Thus, in this study, the study area with transmission line project was selected for 16 cases all over the country to collect satisfaction data from the people who are the owners of the land under the project right of way. The results indicated that 1) type of compensation affect the different level of satisfaction and also factors of information delivery process. 2) the form of participation is the key element to gain acceptance and satisfaction with the project. Therefore, to reduce the impact of development projects and increased satisfaction of citizens should be encouraged to participate in the public perception and comment on the project. Including giving knowledge to residents within the transmission line network securely, which would be another way to raise the level of satisfaction with the community from transmission line network construction.